Fine-Root Turnover, Litterfall, and Soil Microbial Community of Three Mixed Coniferous–Deciduous Forests Dominated by Korean Pine (Pinus koraiensis) Along a Latitudinal Gradient - Liu, Lu; Yang, Fan; Wang, YuJue; Shen, Xing; Janssens, Ivan A.; Guenet, Bertrand; Xiao, Chunwang (Frontiers in Plant Science, 2019)
Carbon dynamics in forests and in particular in soils are of primary importance in the context of climate change. A better understanding of the drivers controlling carbon storage is needed to improve climate mitigation strategies. Carbon storage is the result of a balance between inputs and outputs. Carbon inputs in the soil come from plant residues and root exudates, which are further transformed by microorganisms and stored in the long-term. Here, we measured litter and fine root production in three mixed forests dominated by Pinus koraiensis along a latitudinal gradient, and performed a litterbag experiment to better understand the driving factors of decomposition. We found that over the three sites, litter production was controlled by climatic factors, soil properties and forest stand characteristics, whereas decay rates were mainly controlled by microbial community structure and soil stoichiometry. For fine roots, production differed among sites and higher production was consistently observed in the top soil layers compared to deep soil, although the root distribution along the soil profile differed among sites. Fine root decay rates were mainly controlled by fine-root stoichiometric characteristics. This paper emphasizes the complexity of fine root dynamics even for a single species. Environmental drivers impact on both production and decay and we suggest to perform manipulative field experiments to better identify the mechanisms involved in soil carbon cycling.